Our marvelous bodies : an introduction to the physiology of human health - Merrill, Gary F. (Rutgers University Press, 2008)
Our Marvelous Bodies offers a unique perspective on the structure, function, and care of the major systems of the human body. Unlike other texts that use a strictly scientific approach, physiologist Gary F. Merrill relays medical facts alongside personal stories that help students relate to and apply the information. Readers learn the basics of feedback control systems, homeostasis, and physiological gradients. These principles apply to an understanding of the body?s functioning under optimal, healthy conditions, and they provide insight into states of acute and chronic illness. Separate chapt.